Integrated planning for sustainable building production – an evolution over three decades. Issue 2 (17th February 2017) - Mikaelsson, Lars-Åke; Larsson, Johan
Abstract: This paper reviews the authors' work on Integrated Planning (IP) as a construction site management tool. IP integrates the different planning skills used by site managers, construction workers and craftspersons into an interactive group which manages a production planning process from the earliest stages to the end of a building project. The studies reviewed in this paper, performed over the last three decades, tested, longitudinally evaluated and refined the IP model for use in modern sustainable building sites. The refined model, Integrated Planning for Sustainable Building Production (SBP), includes the factors: leadership, health and safety, quality management and environmental management.